On Dinosaur Reconstruction: The Head - Florides, Georgios A.; Christodoulides, Paul (My University, 2022)
This paper presents the current knowledge about the reconstruction of dinosaur heads. To reconstruct the dinosaur head, several features and functions of the head must be studied, namely osteology, musculature and soft tissue of the head, cranial kinesis, craniodental biomechanical characteristics, posterior part of the cranium, skin, and others. The main steps and points resulting from the study are the following. Firstly, the osteological remains of the head are studied for reconstruction according to the correct size and form in comparison with known remains belonging to the same family in case the remains were not complete. As the dinosaurs did not have facial muscles, their skin was pressed directly to the skull. The skin covering the large openings in front of the orbits of many dinosaurs probably bulged gently outward, and similarly, the jaw muscles bulged gently from the skull openings. Also, an investigation is performed to decide if sauropods were terrestrial or aquatic animals. Then, the individual characteristics of the head are examined in detail. These concern: 1) endocranial cast and nerves, 2) nostrils position, 3) the existence and kind of cheeks and lips, 4) Teeth types and function, 5) the palate shape and skin covering, 6) hyoid apparatus and tongues, 7) the details of the ear, 8) sclerotic rings and eyes, 9) skin and color. With the knowledge gathered about the various parts of the head in mind, decisions are made about the Amargasaurus (a sauropod) head in order to reconstruct a 3D, actual size head, as a worked example. Finally, the reconstruction procedure is described in detail.
Keywords: Amargasaurus reconstruction; Dinosaur head details; Diplodocus skull; Eye; Sclerotic ring; Ear; Head musculature; Teeth; Tongue; Oral cavity; Nostrils; Nostrils; Skin